2019
DOI: 10.1080/14636778.2019.1677149
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and experiences of European clinical geneticists towards direct-to-consumer genetic testing: a qualitative interview study

Abstract: Direct-to-consumer (DTC) genetic tests (GT) enable consumers to access a wide range of GT, without involving a healthcare professional, promoting an increasing disassociation of genetics from the clinical context. This study explores, through semi-structured interviews, the experiences and attitudes of European clinical geneticists towards DTCGT. Our results indicate that the participants have limited experience of consultations with patients regarding such tests.In the majority of cases, the participants stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(31 citation statements)
references
References 41 publications
(48 reference statements)
1
30
0
Order By: Relevance
“…Following exclusion of ineligible records, 25 full texts were reviewed, of which 17 papers met the eligibility criteria (details of 8 excluded full texts are provided in Appendix A ). Two additional papers from other sources were found to fulfil the criteria for inclusion [ 21 , 22 ]. Therefore, 19 new papers were identified in this review.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following exclusion of ineligible records, 25 full texts were reviewed, of which 17 papers met the eligibility criteria (details of 8 excluded full texts are provided in Appendix A ). Two additional papers from other sources were found to fulfil the criteria for inclusion [ 21 , 22 ]. Therefore, 19 new papers were identified in this review.…”
Section: Resultsmentioning
confidence: 99%
“…1 . There were two instances where two reports related to the same study (two newly identified records [ 22 , 23 ], and two identified by Goldsmith et al [ 7 ]. Therefore, this review identified a total of 25 studies that address the knowledge and views of HCPs on DTC-GT for further evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations